A novel DNM2 variant associated with centronuclear myopathy: a case report - Rimoldi, Martina; Velardo, Daniele; Zanotti, Simona; Ripolone, Michela; Del Bo, Roberto; Ciscato, Patrizia; Napoli, Laura; Corti, Stefania; Comi, Giacomo Pietro; Ronchi, Dario (Frontiers in Genetics, 2025)
DNM2 encodes the dynamin-2 protein, a GTPase involved in clathrin-mediated endocytosis and other membrane trafficking pathways. The dynamin-2 protein is composed of several functional domains, including a GTPase domain, a middle domain, a pleckstrin homology (PH) domain, a GTPase effector domain (GED), and a proline-rich domain. Monoallelic variants in DNM2 are associated with Charcot–Marie–Tooth disease and a rare form of congenital centronuclear myopathy (CNM). Several DNM2 variants have been reported in patients with CNM, typically presenting with mild and slowly progressive symptoms. We report the case of a 47-year-old man with DNM2-related myopathy, who presented with progressive muscle weakness starting at the age of 40 years. Clinical exome sequencing revealed the presence of a heterozygous DNM2 variant c.1726G>A, p.(Glu576Lys). This variant, previously unreported, is located in the PH domain of the protein. Muscle biopsy findings showed several fibers with central nuclei, sometimes multiple. In addition, occasional centronucleated fibers showed a radial distribution of sarcoplasmic strands. This study expands the clinical and genetic repertoire of DNM2-related myopathy.